Acolhimento à demanda espontânea: processo de trabalho da equipe de profissionais em unidade básica de saúde - Rodrigues, Maria Sabrinny Martins (2019)
Primary health care is currently the main level of health care for the Brazilian population and one of the main employers of health professionals. One of the activities required in the work processes in Primary Care is the reception of spontaneous demand. Thus, this study, with a qualitative approach, aims to describe the work process in the reception of spontaneous demand in a Primary Health Care Unit in the city of Fortaleza, identifying the knowledge of professionals about the flows adopted and the official regulations, characterizing their potential and challenges and knowing the feelings they experience in this process. Regarding the methodological path, the research used the descriptive exploratory study. Data collection was carried out through a script of semi-structured interviews with eleven health workers. The data analysis had as reference the thematic analysis of content. The study was approved by the Research Ethics Committee of the Federal University of Ceará, with opinion No. 3,525,812. The results revealed that the model adopted by the Municipal Secretariat of Health is oriented to the biomedical model; a standard of care centered on the disease and not on the individual. We identified that in spontaneous demand, many professionals do not use the classification of risks and vulnerabilities for the care of the population, due to the large number of people who seek care. The adopted model and the large number of people to be cared for provoke in professionals feelings of suffering, related to frustration and impotence, making it necessary and urgent for them to review the model of care adopted, taking into consideration and opening space for the worker to expose their opinions and concerns, in favor of improvements in their work processes and overcoming negative feelings arising from their professional practice.